Seismic response reduction of building structures using a semi-active control system based on a a brain emotional learning controller - Braz-César, M.T. (2018)
The present paper investigates the effectiveness of a bio-inspired semi-active controller to reduce seismic-induced vibrations in building structures. The control system is based on the use of a MR damper in combination with the so-called Brain emotional learning based intelligent controller (BELBIC), which is an intelligent controller based on the model of Limbic system of brain. A general case for a three degrees of freedom building structure excited by the El Centro earthquake will be used to demonstrate how a semi-active control system comprising a MR damper in a non-collocated configuration can reduce the structural response under seismic loading. Hence, the key objective of this study will be to evaluate and verify the efficiency of a MR damper in controlling the level of vibrations in a three degrees of freedom building structure by means of a BEL controller. A comparison between uncontrolled and controlled structural responses are used to validate the performance and efficiency of the proposed semi-active controller.